Radiocarbon Chronology of the Inca Expansion in Argentina - García, Alejandro (2021)
The purpose of this article is to broaden the information available on the chronology of the Inca expansion in Collasuyu by analyzing all radiocarbon dates obtained in Argentina’s Inca sites. We evaluated and classified all the dates (n=178) into three different groups (G1, G2, and G3), according to the quantity and quality of contextual information, and the possibility of effectively verifying this information through published articles. The interpretation was mainly based on the dates showing the best information regarding the origin and context of the samples (28 of the G1, and 36 of the G2). Our results indicate that the Inca advance started towards the beginnings of 15th Century AD in the northernmost part of Argentina and rapidly continued southwards, probably reaching the province of Mendoza some 50 years later. This study confirms the differences between the ethnohistoric chronology and the radiocarbon data, previously pointed out by other authors. Moreover, it suggests a sequence of at least three stages in which the Incas would have incorporated the existing territories until ca. 24°, 28°, and 34° 30' S, respectively. This is the first global study of Inca chronology in Argentina, and the first time that dates are classified to determine their level of context information and reliability.